Locating the optimal microstructural state against dynamic perforation by evaluating the strain-rate dependences of strength and hardness. (June 2021) - Wu, S.J.; Qu, R.T.; Liu, Z.C.; Li, H.F.; Wang, X.D.; Tan, C.W.; Zhang, P.; Zhang, Z.F.
Highlights: The strain-rate sensitivity relies on not only materials but also loading modes. The dynamic strength and dynamic hardness exhibit strikingly different trends. The relation between hardness and strength under dynamic loading is established. The change of strain-rate sensitivity reflects the trend of dynamic perforation failure. A criterion for the optimal microstructure against dynamic perforation is proposed. Abstract: Intense research efforts have been made to understand the variation of strength with strain rate, while the mechanisms governing the strain-rate dependence of hardness have been rarely studied. In this work, we conducted a comprehensive investigation on strength, hardness and failure mechanism of AISI 4340 steels with 4 different microstructural states in a wide range of loading rate. We found strain-rate hardening behavior in all 4 steels, while the degree of hardening, characterized by the normalized dynamic strength (NDS) or the normalized dynamic hardness (NDH), depends on not only materials but also loading modes. With the increase of material strength, the NDS significantly increases but the NDH decreases slightly. The inconsistency between the variations of NDS and NDH is because the hardness is governed by not only yield strength but strain-hardening ability. Although the yield strength increases as rising strain rate, the strain-hardening ability reduces obviously, particularly for high-strength materials due to shear softening under dynamic loading conditions, which also causes a transition from homogeneous deformation to shear fracture. The variations of NDS and NDH could reflect the trends for resisting not only the ductile perforation (strength limited) but also the shear plugging failure (toughness limited), allowing to propose a criterion for locating the optimal strength-toughness combination against dynamic perforation, which was further verified by the ballistic penetration testing results. Moreover, similar behaviors of NDS and NDH of various other alloys were also found, which may suggest the extensive applicability of the current approach.